Dissection of surface area-dependent lipolysis at a single organelle level - Chengxin Ma; Yan Liang; Xinmeng Che; Yuqi Li; Jin Wu; Li Xu; Hongyuan Yang; Tong-Jin Zhao; Feng-Jung Chen; Peng Li (Cell Reports)
Summary: Lipid droplets are dynamic organelles whose size and number signify their role in energy. However, owing to cellular heterogeneity and technological limitations, the relationship between the lipolytic ability and lipid droplet morphology is unclear. Here, we developed a live-cell imaging assay using geometric analysis to quantify cellular lipolysis at a single organelle level, designated imaging lipolysis. Using imaging lipolysis and super-resolution imaging, we found that lipolysis is controlled by both lipase-accessible lipid droplet surface area and lipase activity. Moreover, lipid droplet fusion regulatory proteins CLSTN3β/CIDEs promote lipolysis by increasing the total lipid droplet surface area-to-volume ratio in biophysical regulation. We further identified that brown adipocytes exhibit more efficient lipolysis due to higher lipase activity and a larger lipid droplet surface area-to-volume ratio compared to white adipocytes. Taken together, imaging lipolysis generally enabled single-cell lipase activity measurement and revealed a mechanistic basis for energy-generating brown adipocytes to enforce a multilocular phenotype for lipolysis.